Detection of Lr19/Sr25 in segregating populations of wheat (Triticum aestivum L.) using robust molecular markers - Pal, Dharam; Bhardwaj, Subhash Chander; Khan, Hanif; Patial, Madhu; Yadav, Ram Niwas; Sharma, Pratima; Kumari, Shilpi (Journal of Cereal Research, 2021)
Marker assisted breeding (MAB) technology has been proved effectiveto transfer the genes of interest and also increased the accuracy ofselection in wheat improvement programmes. The Agropyron elongatumderived 7D.7Ag translocation carrying Lr19/Sr25 is not only effectiveagainst leaf rust pathotypes but also effective against stem rust raceUg99 and its variants. Therefore, wheat breeding lines carrying Lr19/Sr25 translocation segment have been developed worldwide. Thepresent study was aimed for developing wheat genotypes with Lr19/Sr25 using Xwmc221, PSY1-E1 and Gb DNA markers in segregatingpopulations of wheat. We could infer that Xwmc221, PSY1-E1 andGb are effective molecular markers to tag Lr19/Sr25 in segregatinggenerations of wheat. The data also revealed consistency betweenhost pathogen interaction (HPI) test and Xwmc221, PSY1-E1 and Gbmolecular markers for selecting lines with Lr19/Sr25 in segregatinggenerations. This work not only confirmed the robustness of thethree Lr19/Sr25 markers but also demonstrated the application ofboth genotyping and phenotyping in making full-proof selection ofsuperior progenies with gene of interest in wheat.